2014
DOI: 10.1007/s40071-014-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to agricultural pesticides impairs growth, feed utilization and energy budget in African Catfish Clarias gariepinus (Burchell, 1822) fingerlings

Abstract: The African catfish Clarias gariepinus is a widespread species in the Beninese cotton basin. In this study, the impacts of exposure to agricultural pesticides endosulfan [Thionex 350 EC (emulsifiable concentrate)] and Tihan 175 O-TEQ (oil toxicity equivalent) on growth, feed utilization and energy budget of C. gariepinus were investigated. Fingerlings (1.58 ± 0.02 g) were exposed to borehole water (control), 0.23 ppb (environmental concentration), 440 ppb (Lethal Concentration 50 %/20, LC50/20) and 880 ppb (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, our result agreed with those reported by CA Laetz, DH Baldwin, TK Collier, V Hebert, JD Stark and NL Scholz [ 82 ] who indicated that histopathological damage to the liver, pancreas, and intestine may result in decreased feed digestion and metabolism efficiency because these tissues play critical roles in the regulation of biochemical parameters, particularly proteins, lipids, carbohydrates, and hormones, as well as the synthesis and secretion of digestive enzymes. Other important factors that explain the delay in fish growth could be the transformation into the energy of a portion of nutrients from the digestion of feed consumed to cope with chemical stress that constitutes the exposure to agricultural pesticides [ 83 ] . The highest reduction in growth in the combined agrochemical exposed group may be attributed to a synergistic impact between glyphosate and malathion; this effect could be explained in light of the fact that binary pesticide combinations generated synergistic acetyl-cholinesterase inhibition [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our result agreed with those reported by CA Laetz, DH Baldwin, TK Collier, V Hebert, JD Stark and NL Scholz [ 82 ] who indicated that histopathological damage to the liver, pancreas, and intestine may result in decreased feed digestion and metabolism efficiency because these tissues play critical roles in the regulation of biochemical parameters, particularly proteins, lipids, carbohydrates, and hormones, as well as the synthesis and secretion of digestive enzymes. Other important factors that explain the delay in fish growth could be the transformation into the energy of a portion of nutrients from the digestion of feed consumed to cope with chemical stress that constitutes the exposure to agricultural pesticides [ 83 ] . The highest reduction in growth in the combined agrochemical exposed group may be attributed to a synergistic impact between glyphosate and malathion; this effect could be explained in light of the fact that binary pesticide combinations generated synergistic acetyl-cholinesterase inhibition [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased energy used by S. senegalensis exposed to lower 4-MBC through increased swimming distance can be associated with effects on energetic budget. In fact, effects of chemical stressors on energetic balances have already been reported (Agbohessi et al, 2014;Rabasa and Dickson, 2016;Anacleto et al, 2018). Such excitatory swimming response after 4-MBC exposure may also have later implications on growth or successful feeding and reproduction.…”
Section: Behaviormentioning
confidence: 94%
“…
For a meaningful interpretation of toxic effects in fish, knowledge of sub-lethal events is essential and for this reason, we have conducted a series of studies with a relevant environmental concentration of a mixture of herbicides; Atrazine, simazine, diuron and isoproturon (ASDI) pollutants and using immune (Fatima et al 2007) and endocrinological changes as principal endpoints under controlled laboratory conditions. Goldfish (Carassius auratus) were exposed to a cumulative concentration of 50µg/l of ASDI mixture for 12 weeks which was reported above the permissible level in the drinking water of Belgium (EAEW report, 1998) and nearby aquatic environments, confirming some of these herbicides still persistence despite restriction policies (Pesce et al 2010;Agbohessi et al 2014). Control and exposed fish were sampled at week-4, 8, and 12.
…”
mentioning
confidence: 91%